Delayed thromboembolic events after coiling of unruptured intracranial aneurysms in a prospective cohort of 335 patients. (7th September 2020) - Pierot, Laurent; Barbe, Coralie; Herbreteau, Denis; Gauvrit, Jean-Yves; Januel, Anne-Christine; Bala, Fouzi; Ricolfi, Frédéric; Desal, Hubert; Velasco, Stéphane; Aggour, Mohamed; Chabert, Emmanuel; Sedat, Jacques; et al.
Abstract : Background: Coiling is the first-line treatment for the management of unruptured intracranial aneurysms (UIAs), but delayed thromboembolic events (TEEs) can occur after such treatment. ARETA (Analysis of Recanalization after Endovascular Treatment of Intracranial Aneurysm) is a prospective multicenter study conducted to analyze aneurysm recanalization. We analyzed delayed TEEs in the UIA subgroup. Methods: Sixteen neurointerventional departments prospectively enrolled patients treated for ruptured and unruptured aneurysms between December 2013 and May 2015. Participant demographics, aneurysm characteristics, and endovascular techniques were recorded. Data were analyzed from participants with UIA treated by coiling or balloon-assisted coiling. We assessed the rates, timing, management, clinical outcomes, and risk factors for delayed TEEs using univariable and multivariable analyses. Results: The rate of delayed TEEs was 2.4% (95% CI 1.0% to 4.6%) in patients with unruptured aneurysms, with all events occurring in the week following the procedure. In multivariate analysis, two factors were associated with delayed TEEs: autosomal dominant polycystic kidney disease (ADPKD): 20.0% in patients with ADPKD vs 1.9% in patients without ADPKD (OR 27.3 (95% CI 3.9 to 190.2), p=0.0008) and post-procedure aneurysm remnant: 9.4% in patients with post-procedure aneurysm remnant vs 1.6% in patients with adequate occlusion (OR 9.9 (95% CI 1.0 to 51.3), p=0.006). We describe modalities of management as well as clinical outcomes. Conclusions: Delayed TEE is a relatively rare complication after coiling of UIAs. In this series, all occurred in the week following the initial procedure. Two factors were associated with delayed TEE: ADPKD and aneurysm remnant at procedure completion. Clinical trial registration: NCT01942512